Pengaruh Model Pembelajaran Generatif Terhadap Hasil Belajar Matematika Berbasis Dimensi Kognitif Taksonomi - Raharjo, Nugroho Edi, Idris Harta, M.A., Ph.D (2014)
The objective of this research is to analyze the influence implementation generative learning model towards learner's achievement in mathematics based on Cognitive Dimension of Bloom's Taxonomy. Population in this research is all learners grade VII in SMP Negeri 1 Kaliwungu and sanples are learners in class VII A as control sample and VII D as experiment sample. Sampling technique used by researcher is Cluster Random Sampling. Data collecting methods in this research is documentation method and test method. Technique of data analysis is Mean Difference Testing; prerequisite test is using Liliefors method to test normality and Bartlett to test homogeneity. The result of data analyzing with significant level 5%, there is influence generative learning model towards learner's achievement in mathematics based on cognitive dimension of bloom's taxonomy with z computation = 2,289.